Digital Capability and Household Economic Resilience Among Urban Women Entrepreneurs - Maghfirah Sari Azis (Universitas Negeri Semarang, 2026)
This study examines the role of digital capability in strengthening household economic resilience among urban women entrepreneurs in an emerging economy. While digital transformation has been widely linked to firm-level performance, its broader socioeconomic implications remain underexplored, particularly in relation to household stability. The objective of this research is to investigate whether digital capability enhances household economic resilience directly or indirectly through business performance. Using survey data from women entrepreneurs in Makassar, Indonesia, the study applies Partial Least Squares Structural Equation Modeling to evaluate the measurement and structural models. The results indicate that digital capability significantly improves business performance, and business performance significantly strengthens household economic resilience. However, digital capability does not exert a direct effect on household resilience; its influence operates through business performance as a mediating mechanism. The findings highlight that enterprise-level productivity functions as a critical transmission channel linking technological capability to household stability. This study contributes to the literature by extending digital capability research beyond firm performance and demonstrating its indirect role in enhancing women’s household economic resilience in emerging urban contexts.